Analyzing and Selecting the Optimal Model for E-Service Quality Measurement in Iranian Network Marketing Companies - Habibollah Danai; Mohammad Fotouhi Ardakani; Samaneh Soleimani; Faranak Ghezavat (Research Synergy Foundation, 2026)
Considering the growth of online shopping, research is needed on network marketing as one of the methods of e-commerce to measure the quality of these services. While previous research has been in the field of quality of e-banking, online stores, or e-learning, and so far, no study has been done on the e-SQ of network marketing companies. Hence, this study primarily aims to evaluate and select an optimal model for measuring e-service quality (e-SQ) in network marketing companies within Bazaryaban Iranian Zamin (BIZ) Company. This survey study has a descriptive-survey research design. The statistical sample was selected from the expert community using the snowball method. The convenience sampling method was used for the second population, including 400 leaders of BIZ. Data were collected using the field method and a questionnaire, and then analyzed using SPSS and Excel. The final quality score for BIZ’s e-services is 68.3, indicating good quality. Accordingly, network marketing companies can shorten the purchase cycle, generate economic savings to increase the relative advantage indicator, establish strong customer interaction through the website or other communication channels to increase the tailored information indicator, and foster a sense of empathy and happiness to improve the emotional appeal indicator.